Emotional Management in Academic Performance in the Area of Language in Students of An Educational Institution in Valledupar - Daza, Lisania Esther Mendoza; Daza, Eglandina Leonor Costa; Camacho, Arinda Rosa Casalins; Anaya, Alexcosisky Armando Castilla; Ortiz, Yeferson Jesús Barrera; Molina, Laura Andrea Castilla (Journal of Posthumanism, 2024)
This article is part of a broader research project, which aims to analyze emotional management in the academic performance of sixth-grade students of the Alfonso López Educational Institution in Valledupar. The study is framed in the positivist paradigm and adopts a quantitative, non-experimental, cross-sectional and descriptive field approach. Two Likert-type instruments were applied within the non-experimental design, allowing the analysis of the variables in their natural state without the intervention of the researcher. The data were collected at a single time, directly from the empirical experience, guaranteeing their authenticity and validity. The results showed that teachers do not promote joy as a tool for adaptation or implement playful activities to improve the mood of students, as for students, they do not always use strategies to manage their learning or enhance their talents and skills.